A New Method for Synthesis of Poly(2,6-dimethyl-1,4-phenylene oxide) and Poly(2,6-diphenyl-1,4-phenyl oxide) - Naser M. Al Andis (Journal of Chemistry)
The polymerization of two monomers 2,6-dimethylphenol and 2,6-diphenylphenol was carried out by an oxidative route in the presence of Cu(I) as a catalyst and amine complex as a solvent assisted by microwave heating. The synthesized polymers were characterized by NMR spectroscopy, differential scanning calorimetry (DSC), and gel permeation chromatography (GPC). It was observed that this process of polymerization gives high yield (98 wt%) of poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) and poly(2,6-diphenyl-1,4-phenylene oxide) (PPPO) with a molar mass of 1180 (M¯n), 1400 (M¯w) and 28000 (M¯n), 46500 (M¯w) gm/mol, respectively. A negligible amount of diphenoquinone was also observed and its dispersity was rather moderate, 1.17 and 1.68, respectively.